Assessing and improving the efficiencies of a steam power plant using exergy analysis. Part 1: assessment. (12th July 2006) - Rosen, Marc A.; Tang, Raymond
Energy and exergy analyses are used to examine the performance of a coal-fired steam power plant and to identify and evaluate possible modifications to improve the efficiency of the plant. The exergy analysis provides a detailed breakdown of the exergy losses (including waste exergy emissions and internal irreversibilities) for the overall plant and its components. The results show that irreversibilities are the largest source of exergy loss for the plant and that the irreversibility rate in the steam generator is much larger than that in the other plant components.